State and Regional Payments Mechanisms - Ingram, James C. (Quarterly Journal of Economics, 1959)
I. The payments mechanism for a single state, 619. — II. Importance of large holdings of generalized claims and an integrated capital market, 626. — III. Implications of this analysis for a group of nations, 629.